Strike - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Santa Cruz:::University place::::::::::::
Silk screen print of a hand with index and middle finger in 'V' shaped peace sign. The word "STRIKE" is superimposed on the wrist toward the bottom of the poster.